Thermal-induced upheaval buckling of concrete pavements incorporating the effects of temperature gradient. (1st June 2018) - Yang, Guotao; Bradford, Mark A.
Highlights: Effects of temperature gradient incorporated in the formulation. Buckling responses of two types of pavements are formulated and investigated. Pavements with different characteristics are analysed. Abstract: Thermal upheaval buckling of continuously reinforced concrete pavements is widely reported around the world in conjunction with the evolution of global warming trends and increasing numbers of prolonged heatwaves, and which may lead to catastrophic scenarios. Such heatwaves may produce a large temperature gradient through the thickness of the pavement, and there is a need to examine the effects of a temperature gradient on pavement buckling. This paper proposes an analytical closed-form model for the thermal upheaval buckling of pavements, with a temperature gradient being embedded in the formulation. The principle of stationary total potential is employed to develop the non-linear equations of equilibrium for the postbuckling response of the pavement, and these equations are solved analytically by considering both the lift-off region and the adjoining region. It is found that the temperature gradient has no influence on a continuous lengthwise-symmetric pavement, so two pavement types are analysed in this investigation, one is a continuous pavement with a joint and the other is a continuous pavement adjoining a rigid structure. The paper demonstrates that a positive temperature gradient will lower the safe temperature of a concrete pavement with a joint, while it raises the safe temperature of a pavement adjoining a rigid structure. The buckling and postbuckling responses of pavements with different characteristics are analysed by considering the temperature gradient; the parameters being the pavement thickness, pavement base and effective weight.